2010
DOI: 10.1002/zoo.20323
|View full text |Cite
|
Sign up to set email alerts
|

Current husbandry of red pandas (Ailurus fulgens) in zoos

Abstract: The endangered red panda (Ailurus fulgens) is held in zoos worldwide. The aim of this study was to examine how red pandas are kept and managed in captivity and to compare it with the management guidelines. Sixty-nine zoos, mainly from Europe but also from North America and Australia/New Zealand, responded to our survey. The results revealed that in general zoos follow the management guidelines for most of the investigated issues. The average enclosure is almost four times larger than the minimum size recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
0
22
2
Order By: Relevance
“…On the other hand, in the present survey, the frequency of feeding on bamboo was not significantly correlated to the total number of litters. But between the present survey and the previous report (Eriksson et al, ), an overlap of the distributions of feeding frequency on bamboo is limited. If the border (multiple times per day) of the distributions is a crucial threshold to satisfy the requirement for reproduction success or longevity, independent analysis of Japanese population cannot validate this hypothesis, but integrated analysis of the whole population including other than Japan enables to do it.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…On the other hand, in the present survey, the frequency of feeding on bamboo was not significantly correlated to the total number of litters. But between the present survey and the previous report (Eriksson et al, ), an overlap of the distributions of feeding frequency on bamboo is limited. If the border (multiple times per day) of the distributions is a crucial threshold to satisfy the requirement for reproduction success or longevity, independent analysis of Japanese population cannot validate this hypothesis, but integrated analysis of the whole population including other than Japan enables to do it.…”
Section: Discussioncontrasting
confidence: 85%
“…Most Japanese zoos fed bamboo two or three times a day; the previous survey reported that bamboo was fed once a day in 68.1% of the zoos surveyed in Europe, North America, and Australia/New Zealand, with the frequency in some zoos being less than once per day (Eriksson et al, ). With respect to food items other than bamboo, the distribution of feeding frequencies in Japanese zoos was almost the same as those in European, North American, and Australian/New Zealand zoos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study on the critically endangered Red Pandas (Ailurus fulgens) in 69 worldwide zoos 10% of the pandas had dental disease. (Eriksson et al, 2010) There are an increasing number of veterinarians trained in the care of domesticated animals that are asked to examine native animals. (Gaynor and English, 1994) The Australian Veterinary Association still has not adopted a care plan for non-domesticated animal dental care (AVDS, 2007).…”
Section: This Research Was Performed To Analysis the Periodontal Healmentioning
confidence: 99%